Current trends and prospects of tidal energy technology - Chowdhury M.S.; Rahman K.S.; Selvanathan V.; Nuthammachot N.; Suklueng M.; Mostafaeipour A.; Habib A.; Akhtaruzzaman M.; Amin N.; Techato K. (Springer Science and Business Media B.V., 2023)
alternative energy; fossil fuel; power generation; tidal current; tidal power; trend analysis